SPECIFICITY OF INSTRUMENTAL KNOWLEDGE IN MODERN SOCIETY - Скиба, І. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The article studies the specificity of instrumental knowledge in modern society. Instrumental knowledge is considered as a kind of means by which modern man mediates his activity. Special attention is paid to the dependence of the specifics of instrumental knowledge on the value-purpose principles of socio-cultural activity. The existence of contradictions in the tendencies of development of modern instrumental knowledge, caused by contradictions of the socio-culture development proper, is substantiated